GIS-BASED SWAT MODELING FOR SURFACE RUNOFF ASSESSMENT TO SUPPORT URBAN FLOOD RESILIENCE IN CENTRAL JAVA, INDONESIA - Sholichah, Putri Amalia, Ms.; Sulistyawati, Endah; Dewi, Susana Paulina (Smart City, 2025)
Surface runoff significantly contributes to environmental hazards such as floods in Indonesia, including in Borobudur District. Based on watershed delineation, the administrative area of Borobudur District is predominantly located within the Sileng Subwatershed. The rehabilitation zones managed by PT Adaro Indonesia are located in several specific areas within this subwatershed. This study utilizes the SWAT (Soil and Water Assessment Tool) model integrated with GIS (Geographic Information System) to simulate surface runoff quantitaively in the Sileng subwatershed, part of the Progo watershed in Central Java Province. SWAT is applied in this research to simulate surface runoff in both watershed and subwatershed contexts. As a physically based model, it must be calibrated and validated to align with observed hydrological data. While the study area itself is rural, it exerts hydrological influence over downstream regions that are undergoing urban development. The SWAT calibration process yielded good model performance (NSE 0.67, RSR 0.58), although validation performance was unsatisfactory (NSE -0.06, RSR 1.03). SWAT simulation on the subwatershed scale consists of 35 HRUs (hydrological respons units) areas, dominantly by mixed forest (FRST) cover with steep slope (>25-40 %) and very steep slope (>40%). Shrubs (PAST) represent the smallest land cover category, predominantly found on very steep slope (>40%). High annual surface runoff category is primarily associated with dryland seasonal crops (AGRR) and residential areas (URBN) on flat slope (≤8%) and gentle slope (>8–15%), covering an area of 499.47 hectares. In contrast, low annual surface runoff category is mostly observed in mixed forests (FRST) on very steep slope (>40%), with a total area of 694.81 hectares. The watershed rehabilitation areas managed by PT Adaro Indonesia are concentrated in zones with low to moderate surface runoff categories. This study offers novelty by integrating GIS-based SWAT modeling with urban flood resilience planning in Central Java.